The Value of Acoustic Backscattering in Determining the Integration Thickness of the Seabed in Yos Sudarso Bay Papua - Sri Pujiyati; Nyoman MN Natih; Baigo Hamuna; Lisiard Dimara (Politeknik Negeri Batam, 2019)
A considerable amount of research has already been conducted into the nature of water on the ocean floor/seabed, ranging from mapping of the seabed, volume backscattering strength (SV) of acoustics on the seabed, classification of the seabed, besides the relationship between the ocean floor and the biota above it with which it interacts. The Yos Sudarso Bay, Jayapura Papua, is a bay with a seabed which faces the floor of the Pacific Ocean and also forms the estuary of the river Anafre which contributes particles that settle on the seabed. This research aimed to collect data in order to understand differences in the integration of water thickness at 0.2 m and 0.5 m besides differences in the types of the substrate based on the results of SV. Data was collected using a single beam echosounder. The acoustic data were collected at 11 stations. The result is interval of value of SV ranged from -37.81dB to -15.62 dB (at the integration of 0.2 m) up to -15.07dB (at the integration of 0.5 m). The value of SV from the gravel was higher compared to the values found in the coarse sand, fine sand, mud mixed with sand or the pure mud. The lowest value of SV was found in the mud substrate. Results showed that thickness integration yielded different results when tested at 0.2 m and 0.5 m on the seabed. Furthermore, it was found that different types of substrate.